Analisis Risiko Kesehatan Lingkungan Sisa Klor (Cl2) pada ZAMP Perumda Air Minum Tugu Tirta Kota Malang - Hanung Sinandi Arista Putra; Isa Ma'rufi; Ellyke Ellyke (Pustaka Kesehatan, 2022)
Zona Air Minum Prima (ZAMP) drinking water produced by the Perumda Air Minum Tugu Tirta Kota Malang can be consumed through taps directly from people's homes or ZAMP ready-to-drink water taps in public facilities. One of the processing processes is by adding chlorine gas to ZAMP water so that if the water consumed by the community is not processed further, there will be residual chlorine that enters the human body. The aim of this study is to analize the health risk due to residual chlorine that enters the human body. This descriptive study examined ZAMP water samples located in 9 public facilities in Sawojajar Malang. The residual chlorine was determined with laboratory test and analyzed with Enviromental Health Risk Assessment (EHRA). The result showed that the average residual chlorine content in ZAMP drinking water is 0.00611 mg/l, with a maximum value of 0.2 mg/L and a minimum of 0.001 mg/L. Risk characterization in the population shows that the risk of residual chlorine through ingestion is less than one (RQs < 1) both in adult and the children's category. There was no risk of exposure to residual chlorine contained in ZAMP within the next 30 years. Efforts to manage the risk of residual chlorine from exposure to residual chlorine in drinking water of ZAMP Perumda Water Drinking Tugu Tirta Malang City are not needed.